Implementation of the ruler drop test online to measure the reaction speed - Hasanah, Fitriatul; Hidayatullah, Fajar; Handayani, Heni Yuli; Putri Purwoto, Septyaningrum (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
The purpose of this study was to find out how the physical fitness aspect of reaction speed in SMPN 1 Bangkalan students can be done online. In this research, the writer will use descriptive research with a quantitative approach. The population in this study were students of SMPN 1 Bangkalan with a total of 30 people. This study used the Quota Sampling technique. The research instrument used in this study was the Ruler Drop Test which was carried out online. This instrument is used to measure aspects of physical fitness, speed of reaction in the eyes and hands. The data collection techniques used in this study were observation, interviews and documentation, of the 3 data collection techniques used because the implementation of this research was carried out online using video conferencing (zoom meeting, google meet, etc.). Based on the results of the research on the implementation of the online ruler drop test to measure the physical fitness aspects of SMPN 1 Bangkalan students on test 1 and test 2, it can be concluded that students who fall into the "Very Slow" category 0%, the "Slow" category 23%, on the test 1 and 0%, on test 2, category "Normal" 47%, on test 1 and 3%, on test 2, category "Fast" 30%, on test 1 and 70%, on test 2, category "Very Fast" 0%, in test 1 and 27% in test 2, so it can be interpreted that SMPN 1 Bangkalan students can do a ruler drop test to measure aspects of physical fitness, speed of reaction online during a pandemic. In carrying out this test students and teachers can still take tests online or remotely.Keyword : Ruler Drop, Daring, Kecepatan reaksiÂ